Peran dan Kedudukan Danantara Dalam Mengelola Investasi Sebagai Badan Sovereign Wealth Fund (SWF) - Muh Farhan Ar Rusyda; Trubus Rahardiansah (PT. Hasba Edukasi Mandiri, 2025)
The development of the investment climate in Indonesia is marked by the establishment of a Sovereign Wealth Fund (SWF) named Daya Anagata Nusantara (Danantara). This study aims to analyze the legal aspects concerning the role and position of Danantara as an SWF entity in Indonesia, while also comparing it with the sovereign wealth funds of Malaysia and Singapore. The research method employed is normative legal research using conceptual and comparative approaches. The findings indicate that Danantara was established based on the mandate of Law Number 1 of 2025 concerning the Third Amendment to Law Number 19 of 2003 on State-Owned Enterprises. As the implementing body, Danantara is tasked with managing SOEs, regulating dividends from investment holdings, operational holdings, and SOEs, and approving the addition or reduction of state capital participation in SOEs sourced from dividend management. The study also compares Danantara with Singapore's Temasek Holdings and Malaysia's Khazanah Nasional Berhad, revealing differences in the establishment and operation of each SWF.